The call to write - Trimbur, John (Wadsworth/Cengage Learning, 2014)
Organized by genres, including memoirs, letters, profiles, reports, commentaries, proposals, and reviews, and including new chapters on multi-genre writing and on writing essays, this innovative rhetoric gives students the practice they need to write in college and in the public sphere. Timely, provocative readings promote social engagement, encouraging students to become involved, through public writing, in their community and in the greater world around them.